2021
DOI: 10.1039/d0nr07707k
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly, stability and conductance of amphotericin B channels: bridging the gap between structure and function

Abstract: Amphotericin B (AmB), one of the most powerful but also toxic drugs used to treat systemic mycoses, is believed to selectively permeabilize fungal cell membranes to ions in a sterol-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…1B/C, and Fig. S12), even though the single length assembly was assumed to be too short to function as an ion channel (14). We also found that intermolecular hydrogen bonds from the amino sugar moieties in AmB-AmB and AmB-Erg provide an important force that stabilizes these ion channels in an active form (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…1B/C, and Fig. S12), even though the single length assembly was assumed to be too short to function as an ion channel (14). We also found that intermolecular hydrogen bonds from the amino sugar moieties in AmB-AmB and AmB-Erg provide an important force that stabilizes these ion channels in an active form (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The average number of AmB molecules per channel assembly is crucial information for determining the three-dimensional (3D) structure of the AmB channel. In the past, this number has often been estimated by channel conductance measurements ( 16 , 17 ) and MD calculations ( 18 ), but the results have been quite widely distributed from 4 to over 10. Fluorine-labeled AmB ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The average number of AmB molecules per channel assembly is crucial information for determining the 3D structure of AmB channels. Previously, this number has been estimated via channel conductance measurements 12,13 and MD calculations 14 , but the results have varied widely from four to more than ten. Fluorine-labelled AmB (Fig.…”
Section: The Number Of Amb Molecules Constituting One Channel Assemblymentioning
confidence: 99%